Improving UAV Radio Control System with 433 MHz Radio Wave Using Lo-Ra based on QCZEK Model Communication System - Juniardi Nur Fadila (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2022)
UAV must have a reliable control system considering the UAV is an unmanned vehicle that relies on human control on the ground. Most of control system used in UAVs uses a 2.4 GHz as it frequency. This frequency has disadvantaged for UAV because it is mainly used for Wi-Fi communication system so when users of UAV’s fly in urban areas where full of Wi-Fi system, there will be interference within UAV control system and Wi-Fi, so failsafe will often occur. From the theory, different frequencies produce different criteria for radiofrequency communication system to synchronize and manage and secure communication between transmitter and receiver. In this study, we will discuss the application of 433 MHz frequency for the control system for UAV. The goal of this research is to establish a reliable control system of UAV when used for the long-range mission. To make this control system, we use the Lo-Ra module with STM32 based Microcontroller designed for QCZEK TX/RX model communication. After several testing on the ground and the air, the purpose system serve 14 % longer distance than TBS system or market build system and 6 times longer distances than 2.4Ghz frequencies.